An investigation of visual search patterns on responding to table tennis serve for skilled players - Ho, Gui Ching. (2013)
Majority of researchers have demonstrated a number of characteristics in visual search pattern differ between skilled and less skilled players but have neglected to examine the difference of visual search pattern within similar skill levels. Even at high level of performance in penalty situations, some skilled players perform significantly better than others. This leads to the question of whether successful players employ different visual search pattern than unsuccessful players within similar level of expertise. Therefore, the present study intends to investigate the visual search pattern employed by skilled players in a table tennis task through manipulating the task difficulty. Six skilled players will be required to return serves in response to a shot delivered by a skilled server to specific target positions under three different accuracy conditions: i) Low Difficulty (LD), any location within one side of the court, ii) Medium Difficulty (MD), a location that is equivalent to a quarter of the court, and iii) High Difficulty (HD), a location that is equivalent to an eighth of the court. The results showed that with increasing task difficulty, the participants’ performance decreased. Additionally, most of the participants fixated on the bat and ball in all conditions. Moreover, their visual search patterns differ.